PENGENALAN DASAR MICROSOFT OFFICE PADA SISWA-SISWI MTS YAPINA BOJONGSARI - Saprido, Noval; Rizky Kencana, Aditya; Dwi Kurniawan, Arma; Taruna, Gilang; Aradea, Hisa; Bagas Ramadhan, Muhammad; Fathan Almajid, Muhammad; Taufiq Raihan, Muhammad; Fahrezi, Ryan; Fadillah Saryanto, Thopas Ahmad (Abdi Jurnal Publikasi, 2024)
Community Service (PKM) is a tangible manifestation of our commitment as students to make a positive impact on the surrounding community. In order to meet the needs and demands of the times, this PKM program will focus on introducing the basics of Microsoft Office. With the rapid development of information technology, the proficiency in basic Microsoft Office skills is no longer just an additional skill but has become an essential necessity. The community service program with the title "Introduction to Microsoft Office Basics for MTS YAPINA Bojongsari Students" involves several stages and methods to achieve the established goals. Training using Microsoft Office focuses on demonstrating the proper use of Microsoft Office applications. After the presentation of the material, students are asked to practice the presented material. Our hope for the future is that students will be more motivated to learn MS Office as it is highly needed in their future endeavors